The Organization Man - Whyte, William Hollingsworth (Book collections on Project MUSE., 2002)
"Recognized as a benchmark, Whyte's book reveals the dilemmas at the heart of the group ethos that emerged in the corporate and social world of the postwar era."--Nathan Glazer.